Characterisation and evaluation of the regenerative capacity of Stro-4+ enriched bone marrow mesenchymal stromal cells using bovine extracellular matrix hydrogel and a novel biocompatible melt electro-written medical-grade polycaprolactone scaffold. (July 2020) - Black, C.; Kanczler, J.M.; de Andrés, M.C.; White, L.J.; Savi, F.M.; Bas, O.; Saifzadeh, S.; Henkel, J.; Zannettino, A.; Gronthos, S.; Woodruff, M.A.; Hutmacher, D.W.; et al.
Abstract: Many skeletal tissue regenerative strategies centre around the multifunctional properties of bone marrow derived stromal cells (BMSC) or mesenchymal stem/stromal cells (MSC)/bone marrow derived skeletal stem cells (SSC). Specific identification of these particular stem cells has been inconclusive. However, enriching these heterogeneous bone marrow cell populations with characterised skeletal progenitor markers has been a contributing factor in successful skeletal bone regeneration and repair strategies. In the current studies we have isolated, characterised and enriched ovine bone marrow mesenchymal stromal cells (oBMSCs) using a specific antibody, Stro-4, examined their multipotential differentiation capacity and, in translational studies combined Stro-4+ oBMSCs with a bovine extracellular matrix (bECM) hydrogel and a biocompatible melt electro-written medical-grade polycaprolactone scaffold, and tested their bone regenerative capacity in a small in vivo, highly vascularised, chick chorioallantoic membrane (CAM) model and a preclinical, critical-sized ovine segmental tibial defect model. Proliferation rates and CFU-F formation were similar between unselected and Stro-4+ oBMSCs. Col1A1, Col2A1, mSOX-9, PPARG gene expression were upregulated in respective osteogenic, chondrogenic and adipogenic culture conditions compared to basal conditions with no significant difference between Stro-4+ and unselected oBMSCs. In contrast, proteoglycan expression, alkaline phosphatase activity and adipogenesis were significantly upregulated in the Stro-4+ cells. Furthermore, with extended cultures, the oBMSCs had a predisposition to maintain a strong chondrogenic phenotype. In the CAM model Stro-4+ oBMSCs/bECM hydrogel was able to induce bone formation at a femur fracture site compared to bECM hydrogel and control blank defect alone. Translational studies in a critical-sized ovine tibial defect showed autograft samples contained significantly more bone, (4250.63 mm 3, SD = 1485.57) than blank (1045.29 mm 3, SD = 219.68) ECM-hydrogel (1152.58 mm 3, SD = 191.95) and Stro-4+/ECM-hydrogel (1127.95 mm 3, SD = 166.44) groups. Stro-4+ oBMSCs demonstrated a potential to aid bone repair in vitro and in a small in vivo bone defect model using select scaffolds. However, critically, translation to a large related preclinical model demonstrated the complexities of bringing small scale reported stem-cell material therapies to a clinically relevant model and thus facilitate progression to the clinic.